2014
DOI: 10.2460/javma.245.12.1382
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for perioperative death in dogs undergoing splenectomy for splenic masses: 539 cases (2001–2012)

Abstract: Marked preoperative thrombocytopenia or anemia and development of intraoperative ventricular arrhythmias were identified as risk factors for perioperative death in dogs with splenic masses. The risk of death may be limited by efforts to prevent thrombotic and coagulopathic syndromes and to control all sources of intra-abdominal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
0
40
2
1
Order By: Relevance
“…[1][2][3][4][5][6][7] The success of treatment for this tumor type has not improved in the last 30 years. 2,8 Approximately 50% of dogs that are treated for splenic HSA with surgery and chemotherapy are alive at 6 months and only 11% are alive at 1 year post-treatment. 5,8 Yunnan Baiyao (Yunnan Baiyao Group, Tianjin, China) is a Chinese herbal supplement with reported antiinflammatory, procoagulant, and wound healing properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] The success of treatment for this tumor type has not improved in the last 30 years. 2,8 Approximately 50% of dogs that are treated for splenic HSA with surgery and chemotherapy are alive at 6 months and only 11% are alive at 1 year post-treatment. 5,8 Yunnan Baiyao (Yunnan Baiyao Group, Tianjin, China) is a Chinese herbal supplement with reported antiinflammatory, procoagulant, and wound healing properties.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Approximately 50% of dogs that are treated for splenic HSA with surgery and chemotherapy are alive at 6 months and only 11% are alive at 1 year post-treatment. 5,8 Yunnan Baiyao (Yunnan Baiyao Group, Tianjin, China) is a Chinese herbal supplement with reported antiinflammatory, procoagulant, and wound healing properties. No studies on the effect of this herb on clinical outcome in dogs with naturally occurring splenic HSA have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Splenectomy is a commonly performed surgical procedure in veterinary practice for both benign and malignant disease. Traditional open surgical splenectomy performed through a celiotomy incision is a well‐tolerated procedure for management of a variety of splenic pathologies . With increasing interest in minimally invasive procedures in veterinary patients, splenectomy has also been attempted by using laparoscopic techniques, and a variety of minimally invasive splenectomy techniques have been documented in both experimental studies using healthy dogs and in a small number of clinical cases …”
Section: Introductionmentioning
confidence: 99%
“…celiotomy incision is a well-tolerated procedure for management of a variety of splenic pathologies. 1,2 With increasing interest in minimally invasive procedures in veterinary patients, splenectomy has also been attempted by using laparoscopic techniques, and a variety of minimally invasive splenectomy techniques have been documented in both experimental studies using healthy dogs [3][4][5][6] and in a small number of clinical cases. [7][8][9] The first description of a laparoscopic splenectomy (LS) being performed in a human patient was published in 1991.…”
mentioning
confidence: 99%
“…Because primary splenic tumors can be treated by means of splenectomy with an acceptable perioperative mortality rate, 11 improvements in survival time are most likely to result from effective medical management of metastatic disease. Several studies [6][7][8]10,[12][13][14][15][16][17] have reported that survival times for dogs receiving doxorubicin-based chemotherapy appear to be longer than historical survival times reported for patients treated with surgery alone.…”
mentioning
confidence: 99%